Ultrasound-Guided Fascia Iliac Compartment Block Anesthesia for Analgesia in Elderly Hip Fractures - Jing, Niu; Quan-Jie, He; Hai-Liang, Yang; Huan, Liu; Zhang, yong-tao (International Journal of Innovative Research in Medical Science, 2023)
Objective: To investigate the effect of ultrasound-guided iliac fascia analgesia on hip fracture in senile patients. Methods: Preoperative and postoperative ultrasound-guided iliac fascia analgesia was performed in elderly patients with hip fracture. Results: The need for additional analgesics after implementation was recorded. Conclusion: Ultrasound-guided fascia iliac analgesia is feasible, safe and effective in elderly patients with hip fracture.